PERBANDINGAN DATA KORBAN FATAL KECELAKAAN LALULINTAS ANTAR-INSTANSI DI PROVINSI JAWA BARAT - Hartanto Susilo, Budi; Santos, Wimpy; Basuki Joewono, Tri (Jurnal Transportasi, 2010)
The coordination among institutions responsible for recording road accident data is weak. It is shown that thefatal accident data for specific locations and/or time periods are reported differently by police offices,insurance companies, and provincial office of health. The aim of this study is to eliminate the difference inthe reported fatal accident data by developing a uniformity method. The proposed method would be able tohandle parallel conversion for adjusting fatality data from the three institutions. The conversion factor willemploy the combination of average values of the parallel conversion factors. Based on the data available inthe Province of West Java, it is found that the value of parallel conversion factors between the police officeand the West Java Provincial Office of Health is 1.31 and between the police office and Jasa Raharjainsurance company is 3.93. The average value of these conversion factors with insurance claim considerationis 2.56 meaning that the real number of fatalities is 2.56 times the amount recorded by the police office.Keywords: road traffic accident, fatalities accident data, and parallel conversion factor